Proteomic changes in various organs of Haemaphysalis longicornis under long-term starvation - Ningmei Wang; Han Wang; Aimeng Ji; Ning Li; Guomin Chang; Jingze Liu; Desmond O. Agwunobi; Hui Wang (Public Library of Science (PLoS), 2022)
Haemaphysalis longicornis (Neumann), a tick of public health and veterinary importance, spend the major part of their life cycle off-host, especially the adult host-seeking period. Thus, they have to contend with prolonged starvation. Here, we investigated the underlying molecular mechanism of tick starvation endurance in the salivary glands, midguts, ovaries, and Malpighian tubules of starved H. longicornis ticks using the data-independent acquisition quantitative proteomic approach to study the proteome changes. Essential synthases such as glutamate synthase, citrate synthase, and ATP synthase were up-regulated probably due to increased proteolysis and amino acid catabolism during starvation. The up-regulation of succinate dehydrogenase, ATP synthase, cytochrome c oxidase, and ADP/ATP translocase closely fits with an increased oxidative phosphorylation function during starvation. The differential expression of superoxide dismutase, glutathione reductase, glutathione S-transferase, thioredoxin, and peroxiredoxin indicated fasting-induced oxidative stress. The up-regulation of heat shock proteins could imply the activation of a protective mechanism that checks excessive protein breakdown during starvation stress. The results of this study could provide useful information about the vulnerabilities of ticks that could aid in tick control efforts. Author summary Ticks are a common blood-sucking parasite, which spread many pathogens that cause serious diseases such as Lyme disease to people. Ixodid ticks can take up to three blood meals in their life. During the long process of waiting for their host in the wild, they have evolved a strong ability to tolerate hunger, which should not take more than a year. To study these tenacious molecular regulatory mechanisms, we conducted the DIA quantitative proteomics technology to perform large-scale protein quantitative research on various tissues of Haemaphysalis longicornis starved for a long time. Through the analysis of thousands of proteins produced by the performed research, the results showed that many proteins in the ticks starved for a long time had expressed quantitative changes such as the increased expression of some synthase enzymes. The large amount of data provided by this study can help to better understand the molecular mechanism of ticks' long-term hunger tolerance. Although this study focuses on finding possible mechanisms for tick starvation resistance at the protein level, the current findings may well have a bearing on research about special activities such as ultra long-distance space travel in the dormant state of the human body in the future.